Profiling of the secondary metabolites and the characterization two novel antilisterial peptides, xenopep and rhabdin, produced by xenorhabdus khoisanae - Booysen, Elzaan (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.